2014
DOI: 10.1117/1.jbo.19.1.017002
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral hemodynamic and oxygenation changes induced by inner and heard speech: a study combining functional near-infrared spectroscopy and capnography

Abstract: Abstract. The aim of this study was to investigate the effects of inner and heard speech on cerebral hemodynamics and oxygenation in the anterior prefrontal cortex (PFC) using functional near-infrared spectroscopy and to test whether potential effects were caused by alterations in the arterial carbon dioxide pressure (PaCO 2 ). Twenty-nine healthy adult volunteers performed six different tasks of inner and heard speech according to a randomized crossover design. During the tasks, we generally found a decrease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 73 publications
(63 reference statements)
0
23
0
Order By: Relevance
“…Similarly, we cannot rule out a role for 65%CO2 in the anagram results. While it is not immediately obvious what that role might be, it is known that unvocalised language tasks can induce changes in blood oxygenation and 65%CO2 (Scholkmann et al, 2014a). In either case, more complete systemic data would allow a better assessment to be made of the extent to which these factors play a role in the fNIRS signals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we cannot rule out a role for 65%CO2 in the anagram results. While it is not immediately obvious what that role might be, it is known that unvocalised language tasks can induce changes in blood oxygenation and 65%CO2 (Scholkmann et al, 2014a). In either case, more complete systemic data would allow a better assessment to be made of the extent to which these factors play a role in the fNIRS signals.…”
Section: Discussionmentioning
confidence: 99%
“…Recent resting-state studies applying fNIRS simultaneously with fMRI [Duan et al, 2012;Niu and He, 2013;Sasai et al, 2012] or without fMRI [Niu et al, 2012;Zhang et al, 2011a;Zhang et al, 2011b] confirmed that fNIRS represents a reliable resting-state imaging method. The importance of measuring PaCO 2 during fNIRS recordings was also discussed recently [Holper et al, 2014a;Scholkmann et al, 2013a;Scholkmann et al, 2013b;Scholkmann et al, 2014b]. …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Even though they did not find characteristic [O 2 Hb] and [HHb] changes due to the different stimulations, they were able to reveal a strongly confounding effect of “respiration‐related‐changes in the partial pressure of CO 2 in arterial blood (PaCO 2 ) on fNIRS‐derived parameters” (Holper et al., ). Changes in PetCO 2 can have significant impacts on fNIRS signals (Scholkmann, Gerber, Wolf, & Wolf, ; Scholkmann, Klein, Gerber, Wolf, & Wolf, ; Scholkmann, Wolf, & Wolf, ). A main reason for this confounding effect in the fNIRS signal might have been that they did not apply short separation regression within their analyses in order to get rid of confounding hemodynamics of the extracerebral layers (Gregg, White, Zeff, Berger, & Culver, ; Saager & Berger, ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in PetCO 2 can have significant impacts on fNIRS signals (Scholkmann, Gerber, Wolf, & Wolf, 2013;Scholkmann, Klein, Gerber, Wolf, & Wolf, 2014;. A main reason for this confounding effect in the fNIRS signal might have been that they did not apply short separation regression within their analyses in order to get rid of confounding hemodynamics of the extracerebral layers (Gregg, White, Zeff, Berger, & Culver, 2010;Saager & Berger, 2005).…”
Section: Extracerebral Task-related Effectsmentioning
confidence: 99%